2013
DOI: 10.1016/j.ccr.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C α Is a Central Signaling Node and Therapeutic Target for Breast Cancer Stem Cells

Abstract: SUMMARY The epithelial-mesenchymal transition program becomes activated during malignant progression and can enrich for cancer stem cells (CSCs). We report that inhibition of protein kinase C α (PKCα) specifically targets CSCs, but has little effect on non-CSCs. The formation of CSCs from non-stem cells involves a shift from EGFR to PDGFR signaling, and results in the PKCα-dependent activation of FRA1. We identified an AP-1 molecular switch in which c-FOS and FRA1 are preferentially utilized in non-CSCs and CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
297
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(317 citation statements)
references
References 36 publications
19
297
1
Order By: Relevance
“…Several reports have connected Fra-1/AP-1 in human breast cancer to increased expression of the EMT-TFs Zeb1 and Zeb2 and to a lesser extent Slug. [12][13][14][15]17 We investigated whether Fra-1/AP-1 and the EMT-TFs also correlated in mouse mammary EMT. Expression of Fra-1 in EpH4 cells induced EMT and increased proliferation, migration and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have connected Fra-1/AP-1 in human breast cancer to increased expression of the EMT-TFs Zeb1 and Zeb2 and to a lesser extent Slug. [12][13][14][15]17 We investigated whether Fra-1/AP-1 and the EMT-TFs also correlated in mouse mammary EMT. Expression of Fra-1 in EpH4 cells induced EMT and increased proliferation, migration and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with reports that Fra-1 affects the proliferation and motility of human breast cancer cell lines 17,42 and that Fra-1 is a critical EMT effector downstream of Ras signalling. 13,14 Ras and TGFβ cooperate to induce and stabilize a mesenchymal switch in EpH4 cells. 21,22,40 Unlike human breast cancer cells where upstream signalling kinases activation is required, 14,16 ectopic Fra-1 expression was sufficient for EMT and tumorigenesis in EpH4 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-200b, which is one of the members of the miR-200 family, has also been reported to have abnormal expression in various types of cancer, including bladder cancer and gastric carcinoma (33,34) PKCα belongs to the protein kinase C family and has been indicated to be involved in tumorigenesis, invasion, metastasis and proliferation (35)(36)(37). Previous studies of breast cancer indicated that PKCα could serve as an effective therapeutic target due to its notable mediator role in cancer (38)(39)(40). Furthermore, upregulation of PKCα results in cancer cell invasion and proliferation (36,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated MMP2, which is regulated by PKC, is tightly involved in glioma invasion (9). Notably, Tam et al studied the role of PKCα in cancer treatment and reported that it has been a major focus for various types of cancer and even cancer stem cells (28). In addition, Hu et al reported that activation of PKCα is also implicated in glioma cell migration (15).…”
Section: A B Cmentioning
confidence: 99%